2009
DOI: 10.1016/j.jcrs.2008.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Corneal melt in lattice corneal dystrophy type II after cataract surgery

Abstract: We report a patient with lattice corneal dystrophy type II, also known as Meretoja syndrome or familial amyloidosis Finnish type, who developed a corneal melt 15 days after uneventful phacoemulsification. Despite conservative treatment, the corneal melt resulted in perforation. Uneventful penetrating keratoplasty was performed, but delayed graft epithelial healing was noticed postoperatively. Corneal button histopathological evaluation confirmed the initial clinical diagnosis. To our knowledge, this is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…23,24 The use of subconjunctival and intravitreal anti-VEGF has been associated with the reduction of corneal nerve parameters 25 and with corneal neurotrophic factors content decrease in mice. 26 In the current case bevacizumab (5 mg/ml) was introduced 6 weeks after the infectious keratitis on the left eye twice a day. It was well tolerated by the patient and showed regression of deep stromal vessels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23,24 The use of subconjunctival and intravitreal anti-VEGF has been associated with the reduction of corneal nerve parameters 25 and with corneal neurotrophic factors content decrease in mice. 26 In the current case bevacizumab (5 mg/ml) was introduced 6 weeks after the infectious keratitis on the left eye twice a day. It was well tolerated by the patient and showed regression of deep stromal vessels.…”
Section: Discussionmentioning
confidence: 98%
“…22,25 However, in end stage disease when complete corneal anesthesia is present as the current case, surgical indications should be cautious due to the possible poor healing process. 26 Penetrating keratoplasty in LCD II was complicated by a neurotrophic persistent epithelial defect and delayed graft epithelial healing. 22 In Mattila et al serie, 25 graft failure occurred in 16 of 31 eyes known cases of familial amyloidosis and resulted from surface complications in 11 eyes and additionally from rejection in 5 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In FIN-GAR registry patients with median age of 62.7 years the prevalence of cataract was 47% and that of glaucoma 23%. Cataract and glaucoma have been associated to AGel amyloidosis [4,6,[29][30][31][32][33][34][35], but this high prevalence in patients was new information received through this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the assumption has been that renal manifestation of AGel amyloidosis are rather rare and mild in heterozygous patients [4][5][6]. However, some patients have developed even a nephrotic syndrome [26,35,41], requiring dialysis or kidney transplantation. On the other hand, homozygous patients have severe renal manifestations and they may suffer from nephrotic syndrome already in their early twenties, progressing to renal failure, dialysis treatment, and death [26,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This form of treatment has been used in several studies following corneal graft procedures. Similarly, several authors have suggested the use of adjuvant MPG to reduce inflammation and to provide protection against further melting. Shan, Wu and Akpek describe a case of sterile corneal melt following Desçemet's stripping endo‐keratoplasty (DESK).…”
Section: Treatmentmentioning
confidence: 99%